2021
DOI: 10.1016/j.stemcr.2021.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Human Pluripotent Stem Cell-Derived Intestinal Organoids Model SARS-CoV-2 Infection Revealing a Common Epithelial Inflammatory Response

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection leading to coronavirus disease 2019 (COVID-19) usually results in respiratory disease, but extrapulmonary manifestations are of major clinical interest. Intestinal symptoms of COVID-19 are present in a significant number of patients, and include nausea, diarrhea, and viral RNA shedding in feces. Human induced pluripotent stem cell-derived intestinal organoids (HIOs) represent an inexhaustible cellular resource that could serve as a valuable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 55 publications
0
23
2
Order By: Relevance
“…Intra-patient variability can result from diarrhea, possibly explained by changed drug solubility and intestinal permeability ( 13 , 14 ). In our study one case reported minor and temporary gastro-intestinal complaints with two loose stools per day, not expected to substantially change absorption ( 15 ), albeit we cannot exclude an effect from SARS-COV-2 on luminal cells ( 16 ). Notably, KTRs on cyclosporin also showed higher cyclosporin trough levels during COVID-19 infection, despite its characteristic of reduced absorption in diarrhea ( 13 ).…”
Section: Discussionmentioning
confidence: 65%
“…Intra-patient variability can result from diarrhea, possibly explained by changed drug solubility and intestinal permeability ( 13 , 14 ). In our study one case reported minor and temporary gastro-intestinal complaints with two loose stools per day, not expected to substantially change absorption ( 15 ), albeit we cannot exclude an effect from SARS-COV-2 on luminal cells ( 16 ). Notably, KTRs on cyclosporin also showed higher cyclosporin trough levels during COVID-19 infection, despite its characteristic of reduced absorption in diarrhea ( 13 ).…”
Section: Discussionmentioning
confidence: 65%
“…The development of iPSC technologies and the resulting differentiated cell models have dramatically accelerated studies of the pathogenesis of SARS-CoV-2 in various organs. Current studies have employed iPSC-derived cells and organoids, including iAT2 cells, cardiomyocytes, pancreatic endocrine cells, lung organoids, brain organoids, intestinal organoids, liver organoids, to investigate the underlying mechanisms of SARS-CoV-2 infection ( Ardestani and Maedler, 2020 ; Bojkova et al, 2020 ; Huang J. et al, 2020 ; Jacob et al, 2020 ; Pei et al, 2020 ; Mithal et al, 2021 ). As COVID-19 could also cause kidney malfunctions ( Chen N. et al, 2020 ), kidney organoids derived from iPSCs may be a potential research model as well ( Phipson et al, 2019 ).…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Furthermore, human iPSC-derived intestinal organoids generate valuable pathological models for studying the underlying mechanisms of intestinal SARS-CoV-2 infection. It is reported that SARS-CoV-2 actively infects both proximally and distally patterned intestinal organoids, thus resulting in production of infectious viral particles and significant transcriptional alterations, such as upregulation of the interferon-related genes, in multiple epithelial cell types ( Mithal et al, 2021 ). Another organoid study shows that SARS-CoV-2 can infect all intestinal cell types investigated except goblet cells, and disrupt intestinal integrity, which might be the cause of diarrhea and other gastrointestinal symptoms associated with COVID-19 ( Krüger et al, 2021 ).…”
Section: Intestinal Organoidsmentioning
confidence: 99%
“…Other studies have monitored responses to infection, such as interferon signaling. Mithal et al ( 49 ) have demonstrated that human intestinal organoids can be infected by the virus, resulting in the stimulation of interferon-related genes, including BST2, OASL, MX1, IFITM1, and IRF7. Bozzo et al ( 50 ) found that the viral spike protein is able to hijack interferon-induced transmembrane proteins (IFITM 1, 2 and 3) for more efficient infection, and interfering IFITMs can suppress viral infection in gut organoids.…”
Section: Covid-19 and Pluripotent Stem Cell-derived Organoids (Psc-de...mentioning
confidence: 99%